55.5k views
5 votes
Does anyone know the answer for the question below.

Does anyone know the answer for the question below.-example-1

2 Answers

5 votes

x³ + x² - x - 10 =

= x³ - 2x² + 3x² - 6x + 5x - 10

= x²(x - 2) + 3x(x - 2) + 5(x - 2)

= (x - 2)(x² + 3x + 5)

(x - 2)(x² + 3x + 5)/(x - 2)

= x² + 3x + 5

User Jvtrudel
by
5.0k points
6 votes

Answer: option D is the answer

Explanation:

Does anyone know the answer for the question below.-example-1
User Hawwah
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.